2021
DOI: 10.3389/fpsyt.2021.667881
|View full text |Cite
|
Sign up to set email alerts
|

Common Brain Networks Between Major Depressive-Disorder Diagnosis and Symptoms of Depression That Are Validated for Independent Cohorts

Abstract: Large-scale neuroimaging data acquired and shared by multiple institutions are essential to advance neuroscientific understanding of pathophysiological mechanisms in psychiatric disorders, such as major depressive disorder (MDD). About 75% of studies that have applied machine learning technique to neuroimaging have been based on diagnoses by clinicians. However, an increasing number of studies have highlighted the difficulty in finding a clear association between existing clinical diagnostic categories and neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
(105 reference statements)
1
2
0
Order By: Relevance
“…In our cohort, ROI alterations were mainly located in the temporal and frontal medial cortex, parahippocampal gyrus and cerebellar structures, with a predilection for the vermis. Our results establish a link between previous fMRI studies in patients with primary depression, showing neural circuitry alterations in the medial frontal cortex, temporal gyrus, hippocampus, thalamus [37][38][39] and cerebellum, 40 and immunohistological studies proving that anti-P bound to neurons in specific areas of mice brains, including the cingulate cortex, the dentate gyrus of the hippocampus and the piriform cortex. 14 Preziosa et al 41 showed that more severe structural global and nodal abnormalities were found in patients with SLE with anti-dsDNA positivity, irrespective of the serum levels.…”
Section: Discussionsupporting
confidence: 87%
“…In our cohort, ROI alterations were mainly located in the temporal and frontal medial cortex, parahippocampal gyrus and cerebellar structures, with a predilection for the vermis. Our results establish a link between previous fMRI studies in patients with primary depression, showing neural circuitry alterations in the medial frontal cortex, temporal gyrus, hippocampus, thalamus [37][38][39] and cerebellum, 40 and immunohistological studies proving that anti-P bound to neurons in specific areas of mice brains, including the cingulate cortex, the dentate gyrus of the hippocampus and the piriform cortex. 14 Preziosa et al 41 showed that more severe structural global and nodal abnormalities were found in patients with SLE with anti-dsDNA positivity, irrespective of the serum levels.…”
Section: Discussionsupporting
confidence: 87%
“…These biomarkers have been developed separately in some studies 16,17 , and other studies assumed a shared background [18][19][20] . In SSD research, few studies have succeeded in developing state markers using neuroimaging, and for staging markers, there is no consensus on biological staging models 21 .…”
Section: Introductionmentioning
confidence: 99%
“…(2) Due to the difficulty and expensive data acquisition, the amount of rs-fMRI data is relatively small. In the Strategic Research Program for Brain Sciences (SRPBS) database, only 255 MDD patients' rs-fMRI data were collected (Yamashita et al, 2021). Since the heterogeneity of brain functional connections in patients with depression varies from person to person Young et al (2016).…”
mentioning
confidence: 99%